The Gandhara sculptures - Burgess, James, 1832-1916 (Bharatiya Pub. House, 1978)
Study of the sculptures of a Buddhist tradition of Indic art, developed at Gandhara (present Kandahar in Afghanistan) under greek influence from the 1st through the 8th century.